The relationship of sociodemographic and clinical characteristics with the length of stay of COVID-19 patients at Dr. R. Soedjono Hospital, Selong, East Lombok - Junaedi , Muhammad; Wirawan, I Made Ady; Adhi, Kadek Tresna (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: By December 2020, 678 confirmed cases of COVID-19 were recorded in East Lombok District, and more are anticipated. The capacity of the available healthcare institutions is now impacted by the inclusion of these cases. In this study, the duration of stay of COVID-19 patients at Dr. R. Soedjono Hospital in Selong, East Lombok will be described, as well as the association between sociodemographic and clinical factors with length of stay. Methods: This is an observational study with a cross-sectional design using medical records of 409 patients who were confirmed positive for COVID-19 then treated in April-December 2020 and declared cured after completed the treatment period. The data collected included the date of admission and discharge of patients, age, gender, marital status, education, occupation, history of comorbidities and laboratory test results. Data analysis was performed using multiple logistic regression. Results: The average length of stay for COVID-19 patients at Dr. R. Soedjono Hospital Selong, East Lombok was 16 days (SD±7,366) and the median was 14 days (IQR=7). Multivariate analysis shows factors for patients being treated for longer time (the average length of stay ≥17 days) were male (AOR=1.87; 95%CI: 1.21-2.86) and low education level (AOR=1.91; 95%CI: 1.19-3.06). Conclusion: The average length of stay of COVID-19 patients in this hospital was quite long at 16 days. Male COVID-19 patients and those with low education have higher likelihood to stay longer in hospital. The hospital should consider this information to improve hospital planning for COVID-19 patients